2012
DOI: 10.1037/a0030174
|View full text |Cite
|
Sign up to set email alerts
|

Risk preferences and aging: The “certainty effect” in older adults' decision making.

Abstract: A prevalent stereotype is that people become less risk taking and more cautious as they get older. However, in laboratory studies, findings are mixed and often reveal no age differences. In the current series of experiments, we examined whether age differences in risk seeking are more likely to emerge when choices include a certain option (a sure gain or a sure loss). In four experiments, we found that age differences in risk preferences only emerged when participants were offered a choice between a risky and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
7
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(172 citation statements)
references
References 60 publications
9
154
7
2
Order By: Relevance
“…The control variables, such as gender and age, are significant in the direction we expected (Croson and Gneezy, 2009;Mather et al, 2012). Males are significantly more risk/ambiguity-seeking than females, while younger individuals are more risk/ambiguity-seeking than older ones, controlling for migration status.…”
Section: Results 1 (Preference Under State Uncertaintymentioning
confidence: 65%
“…The control variables, such as gender and age, are significant in the direction we expected (Croson and Gneezy, 2009;Mather et al, 2012). Males are significantly more risk/ambiguity-seeking than females, while younger individuals are more risk/ambiguity-seeking than older ones, controlling for migration status.…”
Section: Results 1 (Preference Under State Uncertaintymentioning
confidence: 65%
“…This prominence is such that important lines of research have relied upon a weak definition of risk attitudes and the reflection effect. For example, in the study of age differences in decision making, many researchers have focused on whether the reflection effect increases with age (e.g., Mather et al 2012;Tymula et al 2013; for a review and meta-analysis, see Best & Charness, 2015). Overall, results indicate that older adults focus more on maintenance of the status quo and loss avoidance, leading to an increase of the reflection effect (see Best & Charness 2015).…”
Section: Towards the Use Of Strong Risk Attitudesmentioning
confidence: 80%
“…A categorical distinction between risky and riskless options can be found in several empirical studies: For instance, Schneider and Lopes (1986) found the reflection effect to be extremely irregular when individuals had to choose between pairs of multiple-outcome lotteries (see also Levy, 2010; but see Budescu & Weiss 1987). More recently, Mather et al (2012) showed that younger and older adults manifested the reflection effect when comparing between lotteries (in line with Budescu and Weiss 1987), but noted that both age groups only differed in their risk attitudes when one of the options available was a certain outcome.…”
Section: Towards the Use Of Strong Risk Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior meta-analysis on the general framing effect highlighted this issue, noting that common framing paradigms overrepresented low probabilities in gain-framed scenarios and high probabilities in loss-framed scenarios as a consequence of keeping expected values equal across conditions [10]. From the pool of 18 studies used in Best and Charness’s meta-analysis [18], only 5 used designs that included a full range of probabilities for both gain and loss frames, only 1 study [19] reported data by age groups across all probability conditions, and none reported analyses on the influence of probability within a frame. The current study serves as a follow-up to Mather et al [19], specifically focusing on age differences in the effect of framing and the influence of the outcome probability associated with the risky option.…”
Section: Introductionmentioning
confidence: 99%